Are there sustained psychological impacts in women diagnosed with in-situ or early invasive breast cancers? - Braun, Bettina; Tio, Joke; Krause-Bergmann, Barbara; Hense, Hans-Werner (Frontiers in Global Women's Health, 2023)
Purpose: The detection of a ductal carcinoma in-situ (DCIS) or an early invasive breast cancer (EIBC), particularly by population-wide mammography-screening-programs (MSP), is controversial as an unknown proportion of these cases may be due to overdiagnosis. We investigated whether women with such potentially overdiagnosed breast cancers suffer from sustained adverse psycho-social consequences. Methods: Standardized questionnaires were mailed to 900 survivors, diagnosed with either DCIS or EIBC, requesting self-reports on quality of life using EORTC QLQ BR-23 and C-30. Levels of anxiety and depression were assessed using the HADS questionnaires. Item score values in the study group were compared to reference data obtained from normative studies in the German female reference population. Results: The 577 women who returned completed questionnaires had a mean age of 65.1 years, 387 (67%) had been diagnosed in a MSP. Median time since diagnosis was 5.9 years. There were no substantial differences between the study sample and the reference population for most of the items. While most score values were even slightly more favorable in the study group, the scores for cognitive function were moderately lower, especially among younger patients. Score values for anxiety were generally higher among younger women (50 to 59 years) from the study group, while depression scores were consistently lower. Conclusions: This study indicates that the diagnosis of DCIS or EIBC, which is predominantly a result of the current MSP, does not seem to induce sustained, adverse psychological impacts in affected women when compared with the respective general female population. Of note, only anxiety levels remained elevated even five and more years after diagnosis among younger women .